INOVASI DESAIN KEMASAN BERBASIS TREN VISUAL UNTUK MENARIK KONSUMEN DI PASAR - Andi Fitra Suloi; Arga Ramadhana; Nurmiati Nurmiati; Marchelyn Pongsapan (Universitas Muhammadiyah Kudus, 2026)
Product packaging plays a crucial role in protecting products while enhancing their attractiveness and market value. In the national market, packaging design functions as an essential visual communication and promotional tool. However, many micro, small, and medium enterprises (MSMEs) have not fully optimized the potential of packaging due to limited knowledge, technology, and resources. The challenges faced by the partner enterprises include the use of simple and conventional packaging designs, limited understanding of packaging functions, constraints in human resources and design technology, and the absence of a strong visual identity. The purpose of this activity is to improve the packaging design skills of business actors and to assist MSMEs in increasing their competitiveness in the market. The program began with surveys and direct observations at production sites to identify the actual conditions of processing activities, the challenges encountered by MSMEs, and the quality of existing packaging, which was found to be relatively basic. The observation results indicated that MSME actors required enhanced understanding of packaging functions, sanitation, visual identity, and branding techniques. The next stage involved workshops and training sessions that provided materials on the strategic functions of packaging, visual design elements, labeling techniques, and examples of modern packaging. Through discussions and hands-on practice, participants gained new insights into the importance of packaging as a product communication tool and a marketing strategy. Design mentoring was then conducted intensively to assist MSMEs in developing more professional packaging designs. Participants were facilitated in using design software and produced several new packaging concepts that were more attractive, informative, and featured a strong product identity. A significant increase in participants’ knowledge was observed, rising from only 23% who understood the importance of packaging prior to the activity to 72% after the training.